Periodontal surgery intervention for gingival smile correction - Case report - Sangalette, Beatriz S.; Vieira, Larissa V.; Verri, Felippo R. [UNESP]; Mestrener, Leandro R. [UNESP]; Mestrener, Sandra R. [UNESP]; Toledo, Gustavo L.; Magro, Miriam Graziela; Piras, Fernanda F. (Bentham Science Publishers, 2020)
Introduction: The success of anterior rehabilitation requires more skills than knowledge. It is necessary that the professional has updates on a new approach to obtain the best result considering the high degree of the exigency of these cases. The relationship between red and white esthetic is known and consolidated in the literature. Then, to achieve success in an esthetic smile is indispensable to apply periodontal surgery associated with restorative technique. Methods: In this report, a 28-year-old female patient sought care in a private clinic with a major cosmetic complaint due to disproportion of the clinical crown and gingival smile. Result: After planning, a clinical crown increase was performed, followed by the labial repositioning technique after the healing time of the initial surgery. Conclusion: It can be concluded that some of the surgical techniques, demonstrated in the literature, for gingival correction are feasible when correctly indicated. The best esthetic results will be achieved when the professional can understand the necessity to correct the disharmony of white and red esthetic.
Keywords: Dental; Dentistry; Esthetics; Gingivectomy; Mouth rehabilitation; Periodontics